Microbial eczema: up-to-date topical treatment with silver sulfathiazole - A. L. Bakulev; S. S. Kravchenya; A. N. Platonova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal. The authors conducted a comparative assessment of the efficacy and safety of 2% silver sulfathiazole in a prospective parallel-group observational study of patients with microbial eczema at the exacerbation stage. Materials and methods. The efficacy of the therapy was assessed on Day 7 and Day 14 based on dynamic calculations of the EASI index and ultrasonic assessment of the intensity of pathological processes in the epidermis and derma; the life quality was assessed based on DLQI and EQ-5D indices, respectively. The microbial composition in the lesions was assessed based on bacterioscopy tests of the contents of blains and erosion fluids. The safety of the therapy was assessed based on the frequency of adverse effects. Results. The administration of 2% silver sulfathiazole arrested both eczematous and pyogenic processes in the lesions within a short period of time, which was confirmed by ultrasonic tests: the depth and density of epidermis and derma were normalized. When applications were performed twice a day, the efficacy with regard to gram-positive bacteria was higher as compared to "classical" topical antibiotics. An evident therapeutic effect with regard to gram-positive bacteria and absence of adverse effects substantially improved the life quality of patients suffering from microbial eczema.